Pilot-scale phosphorus recovery from mobile toilet wastewater in Bangkok, Thailand - Thanakrit Neamhom; Pakasinee Yakam; Chalermkiet Bathbumrung; Wirunya Tachavarong; Varakorn Kosaisavee; Yada Pinatha (Scientific Reports)
Abstract The objective of this study is to enhance the capacity of struvite-phosphate forming reactor utilized in the production of phosphorus fertilizer from wastewater collected from mobile toilets, characterized by phosphorus (P) concentrations of 5.0 ± 1.1 g/l. The experimental procedure comprised three sequential phases: the first phase involved the precipitation of struvite-phosphate using the forming reactor; the second phase focused on pelletizing the P product with sugar milling wastes as filler; and the third phase involved assessing the bioavailability of P in agricultural soils. Experimental design entails batch experiments with the operational variables including the Mg:P molar ratio and pH. Results from nine experiments (3 × 3) indicate that (1) the percentage of phosphorus recovery ranged from 1.9 to 65.2, with a peak observed at high pH values, (2) optimal phosphorus recovery is attained at Mg:P ratio of 1.25 and pH of 9 during precipitation, and (3) the EDS analysis confirms the presence of major elements with phosphorus constituting the predominant component at 13.1%weight. Moreover, P leaching in soil predominantly occurred after the 7th day among the various soil types with the 90-days dissolution efficiency in soil of 97.7 ± 0.6, 86.9 ± 4.1, and 88.0 ± 3.0 for sandy loam, silt loam, and clay loam, respectively. These findings underscore the viability of achieving substantial phosphorus recovery through the utilization of a struvite-phosphate forming reactor via chemical precipitation, with additional evidence suggesting effective leaching of pellets in sandy loam soil, thereby highlighting its potential for widespread implementation in both phosphorus recovery and struvite fertilizer production on a large scale.